Macro-Economic Change and Household Financial Strain in Europe 2006-2022 - Cathal O'Donoghue; Zeynep Gizem Can; Ana Montes-Vi\~nas; Denisa Maria Sologon (Institute of Labor Economics (IZA), 2025)
This paper examines trends in household financial strain across Europe from 2006 to 2022, a period marked by three major economic shocks: the 2008 financial crisis, the COVID-19 pandemic, and the ongoing cost-of-living crisis. Using a subjective measure of welfare, financial strain, we analyse household responses to these shocks, which affected countries differently over time. Our theoretical framework centres on discretionary disposable income, accounting for non-discretionary expenses such as housing, commuting, and childcare costs, alongside household-specific inflation rates to assess purchasing power. Overall, we find many instances of increased financial strain during the financial and the cost-of-living crisis. While aggregate relationships between the drivers seem logical in many countries, there are many instances where the aggregate relationship is either unexpected in sign or strength, indicating that the relationship is due to distribution-specific changes than to aggregate changes. Our microanalysis corroborates this hypothesis, showing that most of the characteristics incorporated in our theoretical framework are significant and of the right sign, even if aggregate relationships were weak. Housing costs consistently emerged as a key determinant of financial strain; while commuting and childcare costs had a more complex, less predictable impact due to their endogeneity with employment, which is associated with lower financial strain.
Keywords: C63; I31; D31; 330; household financial strain; economic shocks; distributional effects; microsimulation